2011
DOI: 10.1002/eat.20803
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors, correlates, and markers in early‐onset bulimia nervosa and EDNOS

Abstract: Increased awareness of this may help identify those particularly at risk for developing an early-onset of eating pathology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 42 publications
0
14
1
Order By: Relevance
“…When research has been conducted, it has typically focused on BED, where results suggest that binge eating may develop before dieting for early onset BED, and after dieting for later‐onset BED . The literature on BN is much smaller and no significant differences have been found between early and later‐onset cases . However, studies to date have tended to compare groups on prior exposures (e.g., rates of childhood obesity) without examining prospective predictors of risk for each group (e.g., whether obesity predicts risk for early and later‐onset cases).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…When research has been conducted, it has typically focused on BED, where results suggest that binge eating may develop before dieting for early onset BED, and after dieting for later‐onset BED . The literature on BN is much smaller and no significant differences have been found between early and later‐onset cases . However, studies to date have tended to compare groups on prior exposures (e.g., rates of childhood obesity) without examining prospective predictors of risk for each group (e.g., whether obesity predicts risk for early and later‐onset cases).…”
Section: Introductionmentioning
confidence: 99%
“…17,18 The literature on BN is much smaller and no significant differences have been found between early and later-onset cases. 6,19 However, studies to date have tended to compare groups on prior exposures (e.g., rates of childhood obesity) without examining prospective predictors of risk for each group (e.g., whether obesity predicts risk for early and later-onset cases). Results are also limited to treatment-seeking samples, which are unlikely to represent all BN cases.…”
Section: Introductionmentioning
confidence: 99%
“…The bulk of bulimia risk research has been conducted with adolescent girls around the peak age of onset, which is estimated to be age 16 for binge eating (Day, Schmidt, Collier, Perkins, Van Den Eynde et al, 2001; le Grange & Loeb, 2007; Stice, Marti, & Rohde, 2013) and age 18 for purging (Stice, Killen, Hayward, & Taylor, 1998). Consistent with these estimates for the emergence of these symptoms, Stice et al (2013) found the peak age of onset for bulimia nervosa (BN) to be between 16 and 20 years of age, although the age of onset for BN may be decreasing (Smink, van Hoeken, & Hoek, 2012).…”
mentioning
confidence: 99%
“…However, the biological, psychological, and sociocultural milieu varies dramatically over the lifespan. Research suggests that ED risk factors vary across development such that individuals who develop EDs at different ages appear to have different risk factors [98] as well as distinct etiological pathways [99]. For example, some childhood risk factors such as parent-perceived child overweight predict early, but not lateronset EDs [98].…”
Section: Ed Etiology Across Developmentmentioning
confidence: 98%